Estimation of valuation multiples of Spanish unlisted food companies - Ribal, J.; Blasco, A.; Segura, B. (Spanish Journal of Agricultural Research, 2010)
In the valuation of Spanish unlisted companies, the most commonly used methods are the discounted cash flow, adjusted net book value and multiple valuation methodologies. The Spanish food industry mainly comprises unlisted SMEs (Small and Medium Enterprises) whereas the number of listed food companies is very low. In view of these two facts, there is practically no information on valuation multiples in this sector. In this context, a massive discounted cash flow model is created allowing for the obtainment of valuation multiples for small and medium-sized companies. Once the value of each company is obtained, the most common valuation multiples are calculated. The multiples which vary the least, and specifically the EV/EBITDA (Enterprise Value/Earnings Before Interest, Taxes, Depreciations and Amortisation) multiple, which presents the lowest interquartile range [10.32-14.78 in small companies] and coefficient of variation [0.43 in small companies], are most appropriate for use as a contrast and to aid in the valuation of companies. EV/EBITDA harmonic mean equals 11.51 for small companies and 11.88 for medium companies. Upon comparing the distribution of the multiples of small and medium-sized companies, no statistically significant differences were found.